G159(P) Differential effects of dexamphetamine and methylphenidate on symptoms of inattention-overactivity, oppositional-defiant and weight. (7th April 2014) - Poulton, A; Nanan, R
Abstract : Aims: There is evidence that the dose of stimulant medication that optimises behaviour is higher than the optimal dose for improvement in cognitive functioning (Sprague and Sleator 1977). This implies two distinct therapeutic effects that target different symptom groups. We aimed to compare Dexamphetamine (DEX) and methylphenidate (MPH) for efficacy for symptoms of inattention-overactivity (IO), oppositional-defiant (OD) and effect on weight using dose titration to achieve optimal functioning. Methods: Previously untreated children aged 4–12 years with DSM-IV diagnosed attention deficit hyperactivity disorder (ADHD) were treated with DEX (n = 14) or MPH (n = 36). Within predefined limits, the parents titrated the dose for optimal functioning at home and at school or preschool, communicating with the teachers. Symptoms were monitored using the IOWA Conners rating scale completed by the teacher at baseline and after 1 month of treatment. Weight was also monitored after 1 month. Results: Both medications were associated with significant improvements in IO and OD (p < 0.05). After controlling for baseline parameters DEX and MPH had comparable efficacy for treating OD symptoms (p = 0.97), MPH was associated with greater improvements in IO (p = 0.016) and DEX with more weight loss (p = 0.003). After controlling for baseline parameters the reduction in IO showed no significant association with the reduction in OD (p = 0.30). The reduction in OD was significantly associated with the weight loss after correcting for drug and baseline weight (p = 0.003). Conclusions: Our results support the premise that stimulant medication has distinct therapeutic effects on the core features of ADHD and those of oppositional behaviour. We suggest that during titration parents targeted OD symptoms, finding both medications equally efficacious. Our findings also provide evidence of a close relationship between the therapeutic effect of stimulant medication on OD behaviour and the effect on appetite. MPH appeared to be the better medication overall because at the doses used it was more effective for IO and caused less weight loss. Reference: Sprague RL, Sleator EK. Methylphenidate in hyperkinetic children: differences in dose effects on learning and social behaviour. Science 1977;1984323:1274–1276.